Can the integration of a tax-compliant transfer pricing system into the management control system be successful?: Yes, it can!. Issue 2 (3rd June 2019) - Hummel, Katrin; Pfaff, Dieter; Bisig, Benedikt
Abstract : Purpose: This paper aims to draw on Adler and Borys' (1996) concept of an enabling use of bureaucracy to examine how the integration of a single-book tax-compliant transfer pricing system into the management control system is related to the perceived success of that transfer pricing system. Design/methodology/approach: Based on survey data from Swiss multinational firms, the authors test a structural equation model. In addition, the authors conduct interviews with executives from three multinational enterprises. Findings: The authors find that the integration of a tax-compliant transfer pricing system into the management control system may be perceived to be successful in achieving both tax compliance and internal (control) purposes. This is particularly true when the transfer pricing system is transparent and can be amended in the case of fundamental management control problems. Research limitations/implications: The typical shortcomings of a survey-based research apply to this study. Future research could build on this model and more closely investigate the relationship between transfer pricing system integration and an enabling use of the transfer pricing system. Practical implications: Based on this study's findings, the authors recommend that a strong integration of tax-compliant transfer prices into the management control system should be accompanied by internal transparency and the ability to repair the transfer pricing system. Originality/value: Prior research on the integration between transfer pricing and management control systems has either been analytical or based on case studies. This cross-sectional analysis provides reliable insights into different levels of integration, use and the success of transfer pricing systems.